Species-specific variation in mental gland secretions of turtles revealed by proteomic and lipidomic profiling - A. Ibáñez; B. Skupien-Rabian; U. Jankowska; S. Kędracka-Krok; U. Fritz; M. Auer; P. Praschag; A. Martínez-Silvestre; M. Pabijan (The European Zoological Journal)
Chemical signaling through pheromones is an ancient and widespread mode of communication. Turtles and tortoises (chelonians) secrete pheromones via mental (chin) glands and have superior olfactory capacities rendering them a promising group to study the evolution and function of chemical communication in vertebrates. Here, we use state-of-the art proteomics and lipidomics techniques to identify and explore the possible functions of proteins and lipids secreted by mental glands in turtles. We examined four turtle species all from the family Geoemydidae, to understand among-species as well as sexual variation in the composition of mental gland secretions. Differential expression of a relatively small number (ca. 65) of proteins explained a large portion of the proteome variation across species, highlighting the existence of specific signals evolving even in closely related species. Lipidomic analysis revealed high inter-individual variation, but species differences could be attributed to five different lipid classes. The lipids found in mental glands could have a dietary origin or be related to individual condition, but may nonetheless be used in communication. We also examined sex-specific differences in the proteome of a single species (Mauremys leprosa) and found that males expressed a much larger array of proteins than females. Our findings establish a group of candidate proteins potentially involved in chemical signaling in freshwater geoemydid turtles. Alternatively, differently expressed proteins in mental glands could have an indirect link to chemical communication, being involved in pheromone transport and/or antioxidant protection.